Work-family balance, gender and policy - Lewis, Jane (Edward Elgar, 2009)
Looks at the three main components of work-family policy packages - childcare services, flexible working patterns and entitlements to leave from work in order to care - across EU15 Member States, with comparative reference to the US. This work also provides an examination of developments in the UK